Sex Differences in Rate of Axial Elongation and Ocular Biometrics in Elementary School Students - Terasaki H; Yamashita T; Asaoka R; Yoshihara N; Kakiuchi N; Sakamoto T (Clinical Ophthalmology, 2021)
Hiroto Terasaki,1,* Takehiro Yamashita,1,* Ryo Asaoka,2– 5 Naoya Yoshihara,1 Naoko Kakiuchi,1 Taiji Sakamoto1 1Department of Ophthalmology, Kagoshima University Graduate School of Medical and Dental Sciences, Kagoshima, Japan; 2Department of Ophthalmology, Seirei Hamamatsu General Hospital, Shizuoka, Japan; 3Seirei Christopher University, Shizuoka, Japan; 4Nanovision Research Division, Research Institute of Electronics, Shizuoka University, Shizuoka, Japan; 5The Graduate School for the Creation of New Photonics Industries, Shizuoka, Japan*These authors contributed equally to this workCorrespondence: Hiroto TerasakiDepartment of Ophthalmology, Kagoshima University Graduate School of Medical and Dental Sciences, Kagoshima, JapanTel +81 99-275-5402Fax +81 99-265-4894Email teracchi@m2.kufm.kagoshima-u.ac.jpPurpose: To determine the relationship between the ocular biometrics and axial length (AL) elongation and its rate in elementary school children.Methods: This is a prospective observational study of 102 right eyes of third-grade elementary school students who were 8 to 9 years old. All participants underwent measurements of the AL, anterior chamber depth (ACD), and lens thickness (LT) annually for 3 years. The AL elongation during the first half and second half was calculated by subtracting the AL of the 1st year from that at the 2nd year, and AL of the 3rd year minus 2nd year. The total AL elongation (TALE) was obtained by summing up the first and second half AL elongations. The growth rate change (GRC) was obtained by subtracting the first half AL elongation from second half AL elongation. Spearman correlations were used to determine the correlation between the 1st year ocular biometrics and the TALE and GRC.Results: The mean TALE was 0.54 ± 0.26 mm in boys and 0.46 ± 0.31 mm in girls. The mean GRC was 0.00 ± 0.16 mm in boys and − 0.04 ± 0.14 mm in girls. In boys and girls, the TALE was significantly larger in the eyes with myopic ocular biometrics such as a deeper ACD, thinner LT, and longer AL during the 1st year (|r|=0.41 to 0.46, P < 0.05). The GRC was significantly accelerated in the eyes of only the girls with hyperopic ocular biometrics such as a shallower ACD, thicker LT, and shorter AL during the 1st year (|r|=0.31 to 0.41, P< 0.05).Conclusion: In boys and girls, the TALE tends to be larger in eyes with myopic biometrics at the 1st year examination. The GRC tended to accelerate in the eyes with hyperopic ocular biometry during the 1st year only in girls.Keywords: axial elongation rate, axial length, school myopia